Molecular survey of Anaplasma and Ehrlichia species in cattle from Karaman of Turkey, including a novel tandem report of Anaplasma marginale msp1a gene - Aydin, Mehmet Fatih; Ozubek, Sezayi; Aktas, Munir (Ankara Univ Press, 2019)
Tick-borne pathogens cause serious health problems and loss of productivity in domesticated and wild animals. A. molecular study was performed to detect the frequency of infection with Anaplasma/Ehrtichia (A/E) in cattle from Karaman province of Turkey. Venous blood samples were taken from 150 apparently healthy cattle in 2016. After amplification the hypervariable VI region of the 16S rRNA gene of A/E species, a reverse line blot (RLB) assay was performed using species-specific probes. Since some samples gave signal only to A/E catch-all probe, the samples analyzed in terms of major surface proteins (MSPs) of Anaplasma marginale. Genetic diversity and tandem repeat analysis were made for msp1 alpha gene sequences of A. marginale.Anaplasma-like bodies were detected in four (2.66%) animals via microscopic examination. Anaplasma centrale was detected in eight (5.33%) animals via RLB. When the samples were examined in terms of A. marginale msp 1 a gene with semi-nested PCR, a total of nine (6.00%) animals [six of them (4.00%) were positive for A. centrale with RLB] were found to be infected with A. marginale. In addition, the sequences of MSP 1a amplicons revealed one new tandem repeat (Tr70). According to these results, it was determined that A. marginale and A. centrale were found in cattle in Karaman province and this study provided the first evidence of genetic diversity of A. marginale with one new tandem repeat in cattle in the region.
Anaplasma marginale msp1a geninin yeni bir tandem raporunu da içeren, Türkiye’nin Karaman yöresindeki sığırlarda Anaplasma ve Ehrlichia türlerinin moleküler araştırması
Keywords: A. centrale; A. marginale; cattle; Karaman; tandem repeat